Multibook review: Prevention of radicalisation and deradicalisation as tools in the service of security - Alfredo Crespo Alcázar (Revista CIDOB d'Afers Internacionals, 2021)
Reviews of the books: Marrero Rocha, Inmaculada. Soldados de terrorismo global. Los nuevos combatientes extranjeros. Tecnos, 2020. 216 págs. Gómez, Ángel y Vázquez, Alexandra. Extremismo, radicalización violenta y terrorismo. Sanz y Torres, 2020. 304 págs.